Learning and memory deficits in rats induced by chronic thinner exposure are reversed by melatonin - Baydas, G; Ozveren, F; Akdemir, I; Tuzcu, M; Yasar, A (Wiley, 2005)
Thinner is a neurotoxic mixture which is widely used as an aromatic industrial solvent. This product has been shown to cause functional and structural changes in the central nervous system. We investigated the effect of exposure to high concentrations (3000 p.p.m.) of thinner for 45 days (1 hr/day) on cognitive functions and the levels of neural cell adhesion molecules (NCAM) and lipid peroxidation products (LPO) in the hippocampus, cortex and cerebellum of rats. The actions of melatonin on the effects produced by thinner exposure were also tested. Thinner exposure caused a significant increase in LPO (malondialdehyde and 4-hydroxyalkenals) in all brain regions. Melatonin administration significantly reduced LPO and elevated glutathione levels in the brain regions. NCAM (180 kDa) was significantly decreased in hippocampus and cortex of thinner-exposed rats. Furthermore, thinner-exposed rats showed cognitive deficits in passive avoidance and Morris water maze tasks, whereas in the rats chronically treated with melatonin these effects were reversed. This study indicates that treatment with melatonin prevents learning and memory deficits caused by thinner exposure possibly by reducing oxidative stress and regulating neural plasticity.
Keywords: learning; lipid peroxidation; melatonin; neural cell adhesion molecules; thinner